Genotyping technologies for all - Ragoussis, J (2006)
Three and a half million single nucleotide polymorphisms are now publicly available through the International HapMap project, enabling genetic and pharmacogenetic studies involving whole genome or comprehensive candidate gene association approaches. The cost/genotype for these studies has been driven down to levels unimagined only a few years ago albeit under particular conditions. Here, eight commonly used commercially available genotyping assays (TaqMan, SNPstream, SNPlex, hME/iPLEX, MIP, GenChip, Goldengate, Infinium I and II) are briefly presented and their particular strengths and weaknesses as well as their suitability for particular types of studies and the related costs are also discussed. © 2006 Elsevier Ltd. All rights reserved.